Multidisciplinary Approach for Adult Patients With Childhood-Onset Chronic Disease Focusing on Promoting Pediatric to Adult Healthcare Transition Interventions: An Updated Systematic Review - Wakimizu, Rie; Sasaki, Keita; Yoshimoto, Mitsuki; Miyazaki, Akari; Saito, Yumiko (Frontiers in Pediatrics, 2022)
Introduction Owing to improved prognosis, the number of adult patients with childhood-onset chronic disease (APCCD) has increased. In this systematic review, we evaluated a multidisciplinary approach toward APCCD, focusing on promoting pediatric to adult healthcare transition interventions and their effects. Methods We reviewed literature comparing the effects of pediatric to adult healthcare transition interventions in children and adolescents with childhood-onset chronic disease, using PubMed, MEDLINE, and CINAHL, from 2010 to 2021 (keywords: “transition,” “children,” “intervention,” “healthcare,” etc.). The inclusion criteria were as follows: (i) original studies, (ii) studies on pediatric to adult healthcare transition interventions in children with chronic disease, (iii) patients including “adolescents” aged 12 and older receiving intervention, and (iv) studies that included the four elements of the PICO model: Patient/ Problem, Intervention, Comparison and Outcome model. Results After evaluating 678 studies, 16 were selected, comprising topics such as “individual education programs” (n = 6), “group meetings” (n = 6), “active learning using information and communications technology” (n = 2), and “transition clinics” (n = 2). The effects obtained varied, depending on the contents and methods of the intervention. Additionally, there was no evidence of adverse outcomes from these interventions. Conclusions Pediatric to adult healthcare transition interventions provide systematic support for the transition, patient independence, and social participation; thus, they should be adopted based on their expected effects.